2014
DOI: 10.1016/j.cell.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Oligodendrocyte Generation and Myelination in the Human Brain

Abstract: The myelination of axons by oligodendrocytes has been suggested to be modulated by experience, which could mediate neural plasticity by optimizing the performance of the circuitry. We have assessed the dynamics of oligodendrocyte generation and myelination in the human brain. The number of oligodendrocytes in the corpus callosum is established in childhood and remains stable after that. Analysis of the integration of nuclear bomb test-derived (14)C revealed that myelin is exchanged at a high rate, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
384
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(407 citation statements)
references
References 47 publications
10
384
1
Order By: Relevance
“…40 The results reported here sug gest the dynamic potential of an endogenous precursor population for medically induced remyelination in adults with multiple sclerosis. Future work will be needed to establish the longer-term effect of remye- lination on prevention of axonal loss and disability progression, identify the extent of repair that is achievable with more selective and targeted drugs, and define the optimal dosing regimens and duration of treatment.…”
Section: Discussionsupporting
confidence: 56%
“…40 The results reported here sug gest the dynamic potential of an endogenous precursor population for medically induced remyelination in adults with multiple sclerosis. Future work will be needed to establish the longer-term effect of remye- lination on prevention of axonal loss and disability progression, identify the extent of repair that is achievable with more selective and targeted drugs, and define the optimal dosing regimens and duration of treatment.…”
Section: Discussionsupporting
confidence: 56%
“…77 However, in contrast to mice, radiocarbon dating of cells in the human brain has indicated that very few human oligodendrocytes are born after early childhood. 97 These data suggest that adult human white matter plasticity occurs at the level of postmitotic oligodendrocytes rather than via generation of new olidodendrocytes from endogenous OPCs, as has been documented in rodents. 22 Whether this apparent species-specific variability in adult white matter plasticity could impede human remyelination from implanted OPCs after radiation injury will need to be established empirically.…”
Section: Unique Properties Of Human White Mattermentioning
confidence: 80%
“…Following an analogous approach in which proteins were pulse‐labeled with 15 N followed by a chase period with 14 N, the myelin proteins myelin basic protein (MBP), proteolipid protein (PLP), myelin oligodendrocyte glycoprotein (MOG), and 2′,3′‐cyclic‐nucleotide 3′‐phosphodiesterase (CNP) were identified in an unbiased manner among the long‐lived proteins of the brain (Toyama et al, 2013). Although myelin proteins and lipids are probably overall relatively stable, in the long term they appear to be exchanged substantially according to a study conducted on human postmortem brain samples (Yeung et al, 2014). Of note, studies on myelin turnover in the PNS are rather scarce at this time and require further research attention (Sheean et al, 2014).…”
Section: Myelination and Metabolismmentioning
confidence: 99%